Peran Support Group Dalam Mendorong Motivasi Belajar Remaja : Action Research Pada Pelajar Sma X - Afifah, Afra (UI Scholars Hub, 2013)
This study discusses how support group plays a role in encouraging student’s learning motivation with action research approach. Application of support group becomes an alternative to complete counseling approach in dealing with adolescent learning problem in school. After running the program, an evaluation conducted on five students as the object of study. The result showed that student’s awareness on the low of learning motivation as a problem to be solved affects their involvement in the group. Students who have that awareness are able to engage within group well and get benefit from the existence of group.